Evaluation of bioagents against Sclerotinia sclerotiorum causing Sclerotinia rot of Indian mustard (Journal of Oilseed Brassica, 2026)
Among the fungal diseases, Sclerotinia rot caused by Sclerotinia sclerotiorum (Lib.) de Bary, is the most destructive disease of Indian mustard [Brassica juncea (L.) Czern & Coss.], and its management with chemicals is not economically viable, and environmentally safe. Therefore, the present investigations were aimed to carry out the test of bioagents against S. Sclerotiorum under in-vitro and in-vivo conditions. Invitro, screening of bioagents (Bacillus subtilis, Trichoderma harzianum and T. viride) was done by dual culture technique. All the bio agents viz., Bacillus subtilis, T. harzianum, and T. viride were antagonistic to the growth of S. sclerotiorum. Maximum 69.8 % mycelial growth inhibition of pathogen was recorded with T. viride, and minimum mycelial growth inhibition was recorded by Bacillus subtilis (42.2%). Results under field conditions revealed that minimum disease intensity (26.0 %) was recorded with seed + soil application of T. viride followed by soil application of T. viride (35.7 %) as compared to control (68.3 %).